Work characteristics and employee outcomes in local government - Noblet, A.; McWilliams, J.; Teo, Stephen; Rodwell, J. (Routledge, 2006)
The overall objective of this study was to examine the work characteristics that make significant contributions to extra-role performance (as measured by the helping dimension of citizenship behaviour) and employee wellbeing (measured by job satisfaction and psychological health) in a local government. The work characteristics examined were based on the demand-control-support (DCS) model, augmented by organization-specific characteristics. The results indicate that characteristics described in the core DCS are just as relevant to extra-role performance as they are to more traditional indicators of job stress. Although the more situation-specific conditions were not predictive of citizenship behaviour, they made unique contributions to job satisfaction.